The Effect Of Debt To Asset Ratio, Return On Assets, Total Asset Turnover, And Firm Size On Stock Prices (Empirical Study On Building Construction Subsector Companies Listed On The Indonesia Stock Exchange For The Period 2016-2020) - Wilbert Wilbert (EMaBi: Ekonomi Dan Manajemen Bisnis, 2022)
Fluctuating stock price dynamics make the stock price as one of the considerations or benchmarks of investors in investing, taking into account various elements of financial performance. The purpose of this study is to determine how much influence DAR, ROA, TATO, and firm size have on stock prices in building construction subsector companies. Sampling in this study amounted to 7 companies based on purposive sampling methods, with a population of 19 companies that included all building construction subsector companies listed on the Indonesia Stock Exchange for the period 2016-2020. The test results partially show that DAR, ROA, and Firm Size variables have a significant effect on stock prices. While TATO variable has no significant effect on stock prices. Simultaneously the variables DAR, ROA, TATO, and Firm Size have a significant effect on stock prices.